Slimmingfique slimming clinic business financial planning - Arlindo Hartono, Agustinus; Indradewa, Rhian (Junal Ilmu Manajemen, 2024)
The health and beauty services industry in Indonesia, particularly PT Shadeka Cipta Gemilang (Slimmingfique), is experiencing rapid growth and complex challenges. This research uncovers the company's financial and operational planning strategies, including cost budget management, development capital, and profit projections. The analysis involves revenue, marketing cost allocation, human resource management, and risk management, illustrating the company's adaptation to market dynamics. The research explored the impact of regulatory changes on PT Shadeka Cipta Gemilang's planning, demonstrating the company's flexibility and resilience. Best practices, such as information technology integration, improved operational efficiency, and risk management, are identified. On Financial Analysis, projected income statement, balance sheet, cash flow, and financial ratio analysis showed increased profit and asset growth. The research highlighted the feasibility of the investment with increased ROI, short Payback Period, and positive NPV. The findings provide valuable insights for similar companies looking to improve their financial and operational performance in a dynamic industry.